Efecto de la adición de diferentes niveles de Saccharomyces cerevisiae sobre el fermentado de la pulpa de banano (MUSA SPP) - Garcia Alburquerque, Luis Arturo (2024)
The use of agroindustrial byproducts such as banana pulp can significantly contribute to the sustainability of animal production, reducing costs and improving the efficiency of resource use. The objective of the research was to determine how the incorporation of Saccharomyces cerevisiae, urea and ammonium sulfate on the nutritional value of banana pulp (Musa spp.). Seeking to increase the quality of bromatological nutrients with these additives to improve the quality and nutritional stability of the pulp, transforming it into a viable ingredient that satisfies the demand for products of animal origin and contributes to more sustainable, economical and profitable production systems. The experimental research used a completely randomized design with a factorial arrangement, evaluating the levels of each treatment; Saccharomyces cerevisiae 1%, Urea 0,8%, ammonium sulfate 0,1% and Saccharomyces cerevisiae 1,5%, Urea 1%, ammonium sulfate 0,2% on the aerobic fermentation times of banana pulp (Musa SPP) of 2, 4, 6 hours respectively. Resulting in the best bromatological treatment at a time of 6 hours with Saccharomyces cerevisiae 1%, Urea 0,8%, ammonium sulfate 0,1%. Based on the economic analysis of the treatments of this research, the incorporation of Saccharomyces cerevisiae 1,5%, Urea 1%, ammonium sulfate 0,2%, in fermentation times of 4 hours, due to its low energy consumption.